Dyspraxia in clinical education: a review. (21st November 2017) - Walker, Eleanor; Shaw, Sebastian CK; Price, Jim; Reed, Malcolm; Anderson, John
Summary: Background: The stereotype of the student with dyspraxia as 'clumsy and disorganised' may cause clinical teachers to be concerned about the student's performance in a clinical environment; however, if it is understood that dyspraxic students possess many strengths, as well as weaknesses, it may be that some stereotypical myths will be dispelled and more effective support offered to them. This review considers research surrounding the experiences of students and health professionals with dyspraxia within higher education (HE), alongside the personal experiences of EW, in order to inform the development of clinical teachers with respect to their support for learners with dyspraxia. Findings: A literature review found five relevant articles. Four studies focused on HE students and one on doctors. A significant theme was that dyspraxia impaired learning new skills. Doctors with dyspraxia tended not to disclose their condition, for fear of stigmatisation and negative effects on their career. Positive attributes of dyspraxia included resilience and determination to succeed. Two main adaptations to dyspraxia were highlighted; a 'difference' view focusing on individuals' strengths, and a 'medical/deficit' view, focusing on their weaknesses and the negative perceptions of others. Doctors with dyspraxia tended not to disclose their condition, for fear of stigmatisation Discussion and recommendations: It is important for clinical educators to understand and support students with dyspraxia, as clinical environments can be particularly difficult for them. Dyspraxia has both positive and negative effects. Here we discuss the findings of previous studies in the context of EW's personal experiences. We also present a series of practical recommendations, whilst recognising that more research is required to document their impact in clinical education.